The Art of Making Children : the New World of Assisted Reproductive Technology. - Ansermet, Francois (Karnac Books, 2017)
Advances in assisted reproductive technology are producing a new world whose boundaries and implications have yet to be fully explored and understood. New advances are announced and hit the headlines with dizzying regularity, triggering the hopes and aspirations of some, and the fears of others. What is possible? What are the implications? What should be permissible? Who should decide?Medically assisted reproductive techniques were developed to treat sterility and infertility. However, in parallel this has created a demand for applications outside the fields for which these technologies were originally intended. This book explores the issues that surround medically assisted reproduction by addressing them from the perspective of four key areas: the mystery of procreation and the enigma of origin and where we come from; the question of difference and alterity in procreation (be it the breaking down of the notion that one comes from two in heterologous procreation to the aspirations for same-sex procreation, or the blurring of chronology and generations through cryoconservation); the place of destiny, including how to think about individual destinies in an age of increasingly accessible gene sequencing paired with a growing link between procreation and prediction; and an exploration of how clinicians and professionals can respond to the subjective experiences of those who resort to medically assisted reproduction, and the singularity of each person's response to the difficult and complex questions it raises.--Google Books.
Keywords: Human reproductive technology -- Psychological aspects.; Human reproductive technology -- Moral and ethical aspects.; Human reproductive technology -- Social aspects.; Sex role -- Psychological aspects.; Reproductive Techniques, Assisted -- psychology; Procréation médicalement assistée -- Aspect psychologique.; Procréation médicalement assistée -- Aspect moral.; Procréation médicalement assistée -- Aspect social.; Rôle selon le sexe -- Aspect psychologique.; MEDICAL -- Gynecology & Obstetrics.; Human reproductive technology -- Moral and ethical aspects; Human reproductive technology -- Psychological aspects; Human reproductive technology -- Social aspects; Sex role -- Psychological aspects